The Application of Cognitive Learning Theory in the Subject of Islamic Cultural History - Khairatunni'mah. SM (Journal of Educational Research and Practice, 2024)
This study examines the implementation of cognitivist learning theory in the subject of Islamic cultural history (Indonesian: Sejarah Kebudayaan Islam – SKI) at MAN 2 Sleman. This study uses a qualitative descriptive research type, namely a method that describes, describes, and explains the events that occur to the object being studied based on the situation and conditions when the research was conducted. Data collection techniques used in this study were interviews, observations, and documentation. The results of this study indicate that the application of cognitive learning theory to SKI materials can train students to think critically, they will learn to understand examples and materials through the analysis, observations, and understanding they do, especially in understanding historical events in SKI subjects. In addition, the obstacles that SKI teachers may face in implementing cognitive learning in the independent curriculum are that it is difficult to identify students' interests and talents, because they are given freedom in learning. However, as a teacher, maximizing methods, techniques, and media is the main thing that must be considered so that learning objectives can be achieved.